Puppet resting behavior in the Tibetan antelope (Pantholops hodgsonii) - Luo, Yunchao (PLoS One, 2018)
Rest contributes a large part of animals’ daily life, and animals usually rest in two ways, standing or in recumbence. Small or medium sized ungulates bed to rest in most cases, and standing rest is very rare and hardly seen. Here we described a standing rest behavior of Tibetan antelopes (Pantholops hodgsonii) living on the Tibet Plateau which has not been reported before. We named the standing rest behavior Puppet behavior, since the antelope stand still for a certain time. Of the 304 individuals observed, 48.3% (98/203) of adult and sub-adult males expressed the Puppet behavior, whereas only 6.3% (6/96) of females did, indicating an obvious sexual difference. Puppet behavior occurred more frequently at noon and in the afternoon on sunny and cloudy days, meaning that daytime and weather were both influential factors. Puppet behavior was usually accompanied with rumination and sometimes ended with leg-shaking. Our results suggest that Puppet behavior may be an adaptive form of rest, which may serve a thermoregulatory and anti-predation function, and may be simpler and safer than recumbent rest.